Variation in oil composition of Thevetia peruviana Juss 'yellow oleander' fruit seeds - S A Ibiyemi; V O Fadipe; O O Akinremi; S S Bako (Journal of Applied Sciences and Environmental Management, 2004)
Thevetia peruviana J ‘Yellow Oleander' is a potential oil seed (63% oil) and good alternative protein source (37%) for livestock feeds. The plant remains an ornamental plant because of the high level of toxins in the seeds. Thevetia peruviana, a tropical oil-seed plant can be grouped into four varieties based on the number of kernels per fruits; two varieties based on the colour of the flower and three varieties based on the geographical locations. The two-seed variety is the richest in oil (63%); examinations of the oils for variations based on the geographical location show that plants growing in the middle region of Nigeria have the best oil properties. The fatty acid composition of purple colored flowers is slightly higher in unsaturated fatty acids; and oils from seeds of the driest zone was higher in level of total unsaturation of the oil (62.7%).